Using causal loop diagram in understanding financial activities of Malaysia Pension Fund - Sapiri, Hasimah; Ahmad, Nazihah; Aziz, Nazrina; Zainon, Fatinah (GATR Enterprise, 2015)
Objective – The aim of the article is to present the development of a simulation framework which identifies Malaysia Pension Fund main sources as well as the financial activities. Methodology/Technique-Numerous factors influencing the financial condition pension fund is summarized.Based on the set of system factors in literature summarization, causal loop diagram is used to analyse the interrelationships among these factors.Findings – Causal loop diagram shows a relationship between these factors, which can be used in analysing financial condition of a pension fund.In the developed causal loop diagram, it shows the main sources of Malaysia pension fund, the asset allocation, and the future benefit payment.Novelty – The causal loop diagram will then, be used as a dynamic hypothesis of this study and serves as a basis for quantitative models.